Short report: Hospitalization for new‐onset heart failure in survivors of hospitalized COVID‐19 - Vicente Corrales‐Medina; Jordana B. Cohen; Seavmeiyin Kun; Bianca Pourmussa; Ozgun Erten; Joe‐David Azzo; Julio A. Chirinos (ESC Heart Failure, 2025)
Abstract Aims Previous studies have reported an incidence of new‐onset heart failure (HF) among COVID‐19 survivors ranging from 0.7 to 8.5 per 100 person‐years, but they relied on administrative data for outcome ascertainment. Given the public health implications, a more accurate characterization of the HF burden post‐COVID‐19 is important. Methods and results We conducted a prospective cohort study of survivors of hospitalized COVID‐19 and tracked the incidence of new‐onset HF hospitalizations over the 12‐month period following the index COVID‐19 episode. Outcome ascertainment was based on a combination of chart reviews, patient interviews, and pre‐specified clinical, radiographic and laboratory criteria. We identified 2140 survivors of COVID‐19 hospitalization that were free of HF at the time of discharge. Their mean age was 67 years and 48% were Black/African‐Americans. The incidence rate of hospitalized new‐onset HF was 0.5 per 100 person‐years. Higher BMI and dialysis dependency at baseline were significantly associated with HF development. The 1‐year mortality rate was 3%. Conclusions The incidence of new‐onset HF post‐COVID‐19 in our study was lower than in previous reports, despite involving an older population with more comorbidities and/or more severe COVID‐19 overall. Reliance on administrative data for outcome adjudication in prior studies may have led to an overestimation of the HF burden post‐COVID‐19.